2018
DOI: 10.1371/journal.pone.0202252
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing plagiarism in higher education: A comparison of German and Slovene students

Abstract: Over the past decades, plagiarism has been classified as a multi-layer phenomenon of dishonesty that occurs in higher education. A number of research papers have identified a host of factors such as gender, socialisation, efficiency gain, motivation for study, methodological uncertainties or easy access to electronic information via the Internet and new technologies, as reasons driving plagiarism. The paper at hand examines whether such factors are still effective and if there are any differences between Germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 32 publications
3
39
1
9
Order By: Relevance
“…To prevent this problem, teachers need extensive training in the use of detection systems. From a normative perspective, the results of the present study reinforce the opinions of other authors (Jereb et al, 2018) regarding the fact that there must be clear policies regarding plagiarism and its consequences in the academic environment.…”
Section: Discussionsupporting
confidence: 85%
“…To prevent this problem, teachers need extensive training in the use of detection systems. From a normative perspective, the results of the present study reinforce the opinions of other authors (Jereb et al, 2018) regarding the fact that there must be clear policies regarding plagiarism and its consequences in the academic environment.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, in many cultures, grades and results receive more value than the learning process (Lahur, 2004), creating situations where students are more likely to plagiarize instead of learning to secure good grades. As for the social factors that lead might to plagiarism, Jereb et al (2018) found that family and societal pressures of getting high grades are essential factors that influence plagiarism. Additionally, peer culture and peer pressure can play a role in student plagiarism (Hosny & Shameem, 2014;Ma et al, 2008).…”
Section: Cultural and Social Influences On Plagiarismmentioning
confidence: 99%
“…al. 17 , busy schedule, easy accessibility of electronic resources, unwareness of plagiarism instructions, poor knowledge of research writing and lack of penalty are the perceived reasons of indulging in plagiarism by the students and research scholars of NIFTEM. The results of the study conveys that there is need of creating an academic integrity department and develop anti plagiarism policies at the institute level.…”
Section: Discussionmentioning
confidence: 99%
“…al. 17 revealed that busy schedule, easy accessibility of electronic resources, unwareness of plagiarism instructions, poor knowledge of research writing and lack of penalty are the reasons of indulging in plagiarism.…”
Section: Literature Reviewmentioning
confidence: 99%